ANALISA YURIDIS TERHADAP PENERBITAN SERTIFIKAT HAK GUNA BANGUNAN DI WILAYAH LAUT PANTAI INDAH KAPUK 2 - Octaviani, Defitria; Hendrawarman Hendrawarman (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research conducts a juridical analysis of the issuance of Building Use Rights (HGB) certificates in the sea area of Pantai Indah Kapuk (PIK) 2, a geographically reclaimed area. The study uses a normative juridical method. The research findings conclude that: (a) Building Use Rights (HGB) certificates cannot be issued over the sea or waters because, legally, the sea is not an object that can be encumbered with such rights. The "sea fence" case in Tangerang shows that the issuance of the HGB certificate in that area is null and void by law because the land did not exist or its status had a procedural defect; (b) The government must immediately review and revise regulations related to reclamation and coastal area utilization to ensure that these policies align with the principles of justice, legal certainty, and environmental protection. It must also strengthen supervisory bodies and impose strict sanctions against any violations that occur. The main problems addressed in this research are the legal basis for the issuance of HGB certificates in the reclaimed marine area of PIK 2, and the legal implications of such issuance for land ownership status, state rights, and maritime environmental protection. Furthermore, this research also examines the synchronization and harmonization of relevant laws and regulations, ranging from the Basic Agrarian Law, the Spatial Planning Law, the Coastal Zone and Small Islands Management Law, to other implementing regulations governing reclamation and land rights in coastal areas. The legal analysis focuses on aspects of licensing, environmental impact assessment (AMDAL), public participation, and compliance with sustainable development principles. Key problems identified include alleged non-compliance in the licensing process, lack of transparency and public participation in decision-making, and potential negative impacts on coastal ecosystems, such as changes in ocean current patterns, sedimentation, abrasion, and loss of traditional fishermen's livelihoods.